2011
DOI: 10.1371/journal.pntd.0001293
|View full text |Cite
|
Sign up to set email alerts
|

Early Peritoneal Immune Response during Echinococcus granulosus Establishment Displays a Biphasic Behavior

Abstract: BackgroundCystic echinococcosis is a worldwide distributed helminth zoonosis caused by the larval stage of Echinococcus granulosus. Human secondary cystic echinococcosis is caused by dissemination of protoscoleces after accidental rupture of fertile cysts and is due to protoscoleces ability to develop into new metacestodes. In the experimental model of secondary cystic echinococcosis mice react against protoscoleces producing inefficient immune responses, allowing parasites to develop into cysts. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 61 publications
1
73
0
3
Order By: Relevance
“…In the murine model of experimental infection, it has been shown that E. granulosus cysts induce an early Th1-type cytokine profile which is then followed by a shift toward a Th2-type profile (Mourglia-Ettlin et al, 2011). Similar mechanisms have been reported for human cystic echinococcosis (Zhang et al, 2012).…”
Section: Resultsmentioning
confidence: 54%
“…In the murine model of experimental infection, it has been shown that E. granulosus cysts induce an early Th1-type cytokine profile which is then followed by a shift toward a Th2-type profile (Mourglia-Ettlin et al, 2011). Similar mechanisms have been reported for human cystic echinococcosis (Zhang et al, 2012).…”
Section: Resultsmentioning
confidence: 54%
“…Another distinct cell subtype, regulatory T cells (Treg), particularly observed in chronic parasitic infections (e.g., helminths), have a role in preventing immune-mediated damage (33,34). Notably, the immune response pattern can vary during the infection course; in helminth infections, a T H 1 to T H 2 shift is commonly observed in parallel with infection progression, and may also signal the reduced effectiveness of a drug therapy (35,36).…”
Section: Immune Responses To Infection and Cancermentioning
confidence: 99%
“…Primary infection occurs by ingestion of oncospheres, while secondary infection is caused by dissemination of protoscoleces after accidental rupture of fertile cysts (Mourglia-Ettlin et al 2011). Breijo et al (2008 showed that establishment and survival of hydatid cyst is associated with the control of the early inflammatory response which depends on down regulation of complement activation.…”
Section: Discussionmentioning
confidence: 99%